Agreement analysis between critical power and intensity corresponding to 50% in cycling exercise - Kristopher Mendes de Souza; Ricardo Dantas de Lucas; Paulo Cesar do Nascimento Salvador; Lucas Crescenti Abdalla Saad Helal; Luiz Guilherme Antonacci Guglielmo; Camila Coelho Greco; Benedito Sérgio Denadai (Universidade Federal de Santa Catarina, 2016)
The purpose of this study was to determine the level of agreement between critical power (CP) and intensity corresponding to 50% of the difference (50% Δ) between oxygen uptake (VO2) at lactate threshold (LT) and maximal oxygen uptake (VO2max) in untrained subjects during cycling exercise. Fifteen healthy male subjects (age: 26.0 ± 3.5 years; body weight: 76.6 ± 10.4 kg; height: 178.2 ± 7.6 cm) volunteered to participate in the study. Each subject performed a series of tests to determine LT, VO2LT, CP, VO2CP, 50% Δ, VO250% Δ, and VO2max. The values of LT, VO2LT, CP, VO2CP, 50% Δ, VO250% Δ and VO2max were 109 ± 15 W, 1.84 ± 0.23 L.min-1, 207 ± 17 W, 2.78 ± 0.27 L.min-1, 206 ± 19 W, 2.77 ± 0.29 L.min-1, and 3.71 ± 0.49 L.min-1, respectively. No significant difference was found between CP and 50% Δ (t = 0.16; p = 0.87) or between VO2CP and VO250% Δ (t = 0.12; p = 0.90). However, the bias ± 95% limits of agreement for comparison between CP and 50% Δ and between VO2CP and VO250% Δ were 1 ± 27 W (0.3 ± 14.1%) and 0.01 ± 0.24 L.min-1 (0.2 ± 8.9%), respectively. In summary, the mean CP and 50% Δ values were not significantly different. However, considering the limits of agreement between the two intensities, CP estimated based on 50% Δ might result in a remarkable error when the absolute variability of individual differences is taken into account